The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.36462/h.biosci.20209
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cost-Effective Microalgae Harvesting Strategies for the Production of Biofuel and Oleochemicals

Abstract: Microalgae have been explored for sustainable production of biofuel and chemicals. Microalgae is promising feed stock for the production of several oleochemicals. It has the ability to utilize a variety of low cost feed stocks, accumulated large quantities of lipids and variety of value added products in their biomass. One of the major obstacles associated with the conversion of algae into value-added products is harvesting. The harvesting of algae is the most problematic area due to its low sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Magnetic nanoparticles is another better technique for harvesting [42] Mostly utilized lipid extraction method is Bligh and Dyer as said to be quickly approachable to quantification outcome within less timing but more hazardous to environment as well as self-health. But MTBE i.e., Methyl-tert-butyl ether is the better method than the previous method with non-hazardous effect and increase in the extracted lipid [43]. For future perspective role such as to study the characterization from extracted algal biomass production, high resolution nuclear magnetic resonance spectroscopy (HR NMR) or mass spectroscopy technique is used to study the changes of various composition kept in different storage conditions were found in the algal sample.…”
Section: Nutrient Removal Efficiency Of Aquaculture Wastewater With Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles is another better technique for harvesting [42] Mostly utilized lipid extraction method is Bligh and Dyer as said to be quickly approachable to quantification outcome within less timing but more hazardous to environment as well as self-health. But MTBE i.e., Methyl-tert-butyl ether is the better method than the previous method with non-hazardous effect and increase in the extracted lipid [43]. For future perspective role such as to study the characterization from extracted algal biomass production, high resolution nuclear magnetic resonance spectroscopy (HR NMR) or mass spectroscopy technique is used to study the changes of various composition kept in different storage conditions were found in the algal sample.…”
Section: Nutrient Removal Efficiency Of Aquaculture Wastewater With Microalgaementioning
confidence: 99%
“…At the bright side, the microalgae have several unique features like ability to fix CO 2 and convert it into valuable components via photosynthesis, robust growth with high lipid contents. The microalgae harvesting, qualitative and quantitative estimation of lipid has been reviewed [43,47]. The availability of molecular approaches to increase lipid accumulation and recovery has been extensively discussed [48].…”
Section: Microalgae As a Sustainable Future Biofuel Approachmentioning
confidence: 99%
“…The symbiotic relationship between the two organisms occurs with the release of carbon dioxide by yeast via fermentation of sugar, which is then utilized by microalgae and in turn provides nitrogen to the yeast by metabolism [8, 9]. Arathi et al, has elaborated the qualitative and quantitative approaches for lipid estimation, microalgae harvesting and molecular approaches that can be implemented to promote lipid accumulation and recovery [10][11][12]. Recent studies reveal that some nutrients like ferrous sulfate, sodium nitrate, potassium phosphate, etc., affect the growth and lipid yield at speci c concentrations in a co-culture medium [13].…”
Section: Introductionmentioning
confidence: 99%